Effects of macrophages on the proliferation and cardiac differentiation of human induced pluripotent stem cells - Canling Long; Rui Guo; Ruijuan Han; Kang Li; Yanbing Wan; Jiqing Xu; Xiaoyu Gong; Yanqiu Zhao; Xinhuang Yao; Jia Liu (Cell Communication and Signaling, 2022)
Abstract Background Macrophage phenotypes switch from proinflammatory (M1) to anti-inflammatory (M2) following myocardial injury. Implanted stem cells (e.g., induced pluripotent stem cells (iPSCs)) for cardiomyogenesis will inevitably contact the inflammatory environment at the myocardial infarction site. To understand how the macrophages affect the behavior of iPSCs, therefore, improve the therapeutic efficacy, we generated three macrophage subtypes and assessed their effects on the proliferation, cardiac differentiation, and maturation of iPSCs. Methods M0, M1, and M2 macrophages were polarized using cytokines, and their properties were confirmed by the expression of specific markers using reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and immunofluorescence. The effects of macrophages on iPSCs were studied using Transwell co-culture models. The proliferative ability of iPSCs was investigated by cell counting and CCK-8 assays. The cardiac differentiation ability of iPSCs was determined by the cardiomyocyte (CM) yield. The maturation of CM was analyzed by the expression of cardiac-specific genes using RT-qPCR, the sarcomere organization using immunofluorescence, and the mitochondrial function using oxidative respiration analysis. Results The data showed that the co-culture of iPSCs with M0, M1, or M2 macrophages significantly decreased iPSCs’ proliferative ability. M2 macrophages did not affect the CM yield during the cardiac differentiation of iPSCs. Still, they promoted the maturation of CM by improving sarcomeric structures, increasing contractile- and ion transport-associated gene expression, and enhancing mitochondrial respiration. M0 macrophages did not significantly affect the cardiomyogenesis ability of iPSCs during co-culture. In contrast, co-culture with M1 macrophages significantly reduced the cardiac differentiation and maturation of iPSCs. Conclusions M1- or M2-polarized macrophages play critical roles in the proliferation, cardiac differentiation, and maturation of iPSCs, providing knowledge to improve the outcomes of stem cell regeneration therapy. Video abstract